Prospects and Challenges of Franchising Pharmacies in Ghana: A Case Study of Pharmaceutical Wholesalers and Retailers in the Brong Ahafo Region - Mensah, Edwin Agbeko (2012)
A Thesis submitted to the Institute Of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive of Business Administration,